Shear Stress Affects Biofilm Structure and Consequently Current Generation of Bioanode in Microbial Electrochemical Systems (MESs) - Yang, Jiawei; Cheng, Shaoan; Li, Chaochao; Sun, Yi; Huang, Haobin (Frontiers in Microbiology, 2019)
Shear stress is an important factor that affecting the formation and structure of anode biofilms, which strongly related to the extracellular electron transfer (EET) phenomena and bioelectric performance of bioanode. Here, we showed that using the nitrogen sparging to arouse shear stress during anode biofilm formation increased the linear sweep voltammetry (LSV) peak current density of mature anode biofilm from 2.37±0.15 A/m2 to 4.05±0.25 A/m2. Electrochemical impedance spectroscopy (EIS) results showed that the shear-stress-enriched anode biofilm had a lower charge transfer resistance of 46.34 ohm compared to the unperturbed enriched anode biofilm (72.2 ohm). Confocal laser scanning microscopy (CLSM) observations showed that the shear-stress-enriched biofilms were entirely metabolically active, whereas the unperturbed enriched anode biofilm consisted of a live outer layer covering a dead inner-core layer. The biomass and community analyses revealed that the shear-stress-enriched biofilm had a 4 times higher biofilm density (136.0 μg DNA/cm3 vs 27.50 μg DNA/cm3) and twice the relative abundance of Geobacteraceae (over 80% vs 40%) in comparison with those of the unperturbed enriched anode biofilm. These results show that applying high shear stress during anode biofilm enrichment can result in an entirely metabolically active and dense biofilm with a high relative abundance of exoelectrogens and, consequently, better performance.